Peran Citra Merek dalam Menjembatani Kualitas Layanan dengan Harapan Pasien: Hasil Penelitian - Stevany; Mulyani, Erry Yudhya; Noerni, Noerni (Cermin Dunia Kedokteran, 2024)
Patient expectations in the context of modern health services are defined as patient expectations regarding the availability of information, participation in decision-making, and overall service quality. The research aim is to analyze the influence of tangibility, empathy, reliability, responsiveness, and assurance on patient expectations intervened by hospital brand image. The selection used the accidental sampling technique of 200 respondents at emergency room patients using accidental sampling technique. This study employed quantitative methodology, focusing on associative causality through a cross-sectional framework. Data were gathered via questionnaires and analyzed using structural equation modeling—partial least squares (SEM-PLS). The findings suggested that patient expectations were shaped by tangibility, empathy, and responsiveness yet were unaffected by reliability and assurance, with brand image served only to mediate the impact of responsiveness on patient expectations. These outcomes offer insights for hospital administration on the importance of enhancing systems for facility upgrades, technological advancements, and the improvement of human resources through targeted training.